Decentralized Authoritarianism in China The Communist Party’s Control of Local Elites in the Post-Mao Era - Landry, Pierre F (Cambridge University Press, 2013)
Though I did not know it at the time, this book really began in Michel Oksenberg’s office after one of his famous trips to Shandong, on the day he introduced a small group of graduate students to the recently published gazetter of Zouping County. I was impressed by Mike’s enthusiasm, but it was not until Professor Liu Linyuan of the Hopkins- Nanjing Center for Chinese and American Studies agreed to advise me in an independent study that I realized how right Mike really was. Liu laoshi walked me to the Provincial Gazetteer’s Office and convinced me that the systematic study of Chinese local government was possible